Modeling Solubility of Acetylsalicylic Acid in Aspen Plus - Makpal Rakhatkyzy; Botakoz Suleimenova; Minavar Shaimardan; Dhawal Shah; Nuraje Nurxat (Engineered Science Publisher, 2023)
Acetylsalicylic acid is one of the most exchanged pharmaceuticals in the world.However, it was scarcely studied when it was in solution.Solubility of acetylsalicylic acid in ethanol, acetone, propylene glycol, and 2-propanol were determined in the temperature range between 270-360 K using Aspen Plus V14 as for binary systems.Three thermodynamic models (NRTL, UNIFAC, and UNIQUAC) of Aspen Plus were used for the simulations and the results were validated based on previous experimental work by Maia and Giulietti (2008).The results showed that ethanol, propylene glycol, and 2-propanol had excellent agreement between modeled and experimental solubility values, while acetone had little discrepancy, highlighting the need for extensive modeling.The NRTL thermodynamic model outperformed others, especially in ethanol.Temperature-dependent solubility was determined in all solvents, with 2-propanol showing significant similarity between actual and simulated data.Propylene glycol and ethanol gave similar results to the experiments till 310 K and showed slight deviation at high temperatures.This study highlights the relevance of solvent-specific factors and accurate modeling for solubility prediction, providing useful information for medical and chemical applications.
Keywords: Non-random two-liquid model; UNIQUAC; Solubility; UNIFAC; Acetone; Chemistry; Solvent; Thermodynamics; Ethanol; Activity coefficient; Organic chemistry; Aqueous solution; Physics; type of access: open access